Multiple contracts and coordination in international construction projects a Swiss law analysis - Künzle, Jürg (International arbitration law library ;, 2020)
This comprehensive analysis of key legal issues arising from interdependencies between multiple contracts methodically lays out, from a Swiss law perspective, the way in which coordination of works in construction projects could or should occur. It also examines the legal consequences of coordination failure and various related aspects of dispute resolution. Topics covered include the following: interfaces and interdependencies across the system boundaries of multiple contracts coordination responsibilities derived from the principle of good faith and from a contextual interpretation of interdependence-related FIDIC Red Book provisions; delegation scenarios; liability for breach of contract and legal remedies in case of delay, disruption, defects, destruction and performance impossibility; direct claims against third parties; taking of evidence under substantively intertwined contracts; and coordination of interrelated arbitration proceedings. The detailed analysis draws on numerous specific real-life examples as well as illustrative Swiss and Unites States case law. An appendix offers very useful practice pointers. Although considering Swiss law, which is a frequent choice for the law governing international construction contracts, the analysis deals with an array of conceptual aspects of multiple contracts and coordination, thereby addressing a great number of issues beyond the limits of national law.